Pertanggungjawaban Hukum Nadzir Yayasan ZIS Al-Ikhlas dalam Pengelolaan dan Pengembangan Harta Wakaf Berdasarkan UU No. 41 Tahun 2004 - Najla, Elsa; Maharany Barus, Utary; Aprilyana Sembiring, Idha (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Waqf holds an important position in Islam, both as an act of worship with spiritual value and as a socio-economic instrument to support community welfare. However, the practice of waqf management in Indonesia still faces serious obstacles, including the economic limitations of the community, low legal literacy, and the weak capacity of nazhir in developing waqf assets. This condition demands institutional strengthening and legal certainty so that waqf management can be carried out in accordance with Islamic law and Law Number 41 of 2004 on Waqf. This study aims to analyze the legal responsibility of Yayasan ZIS Al-Ikhlas as a nazhir in the management and development of waqf assets, assess its compliance with statutory regulations, and identify the challenges encountered in practice. The research method applied is normative legal research with statutory and conceptual approaches, supported by empirical data obtained through interviews with foundation administrators and related parties. The data were analyzed qualitatively by emphasizing the correlation between legal norms and field implementation. The findings indicate that legal certainty is a crucial aspect in the implementation of waqf to guarantee the protection of all parties’ rights. The role of notaries in drafting the Waqf Pledge Deed (Akta Ikrar Wakaf/AIW) is proven to be highly significant in strengthening waqf legality, as emphasized in Government Regulation Number 42 of 2006. Nevertheless, Yayasan ZIS Al-Ikhlas still faces limitations in asset development planning, managerial transparency, and nazhir resources. Theoretically, this study affirms that nazhir’s legal responsibility not only covers administrative compliance with regulations but also encompasses public and managerial accountability. These findings contribute to the development of waqf legal studies in Indonesia by stressing the importance of professionalizing nazhir, building synergy with legal authorities, and innovating management practices to make waqf more productive and sustainable in supporting community welfare.